Underwater pulsed ultrasound in animal model osteochondral injury - do Rocio Brostulin, Danielle; Pinho, Mauro; Antonio Schueda, Marco (Seven Editora, 2023)
Objective: To study changes in an osteochondral surface, submitted to a standardized mechanical lesion analyzing the use of pulsed ultrasound with a frequency of 1MHz, at 20%, with frequency modulation of 16Hz, 0.5 W/cm2 of intensity, and application time of 5 minutes in these lesions. Method: Sixteen white, male, New Zealand rabbits (Oryctolagus cunicullus) less than six months old, with weight ranging from 1,540 grams (g) to 2,450 with standardized lesions in femoral condyles were used. They were submitted to daily application of pulsed ultrasound at a frequency of 1MHz, at 20%, with frequency modulation of 16Hz, 0.5 W/cm2 intensity and application time of 5 minutes in two groups with two and four weeks of osteochondral lesion. Result: The animal model selected and the formatting of the histological analysis were adequate for the proposed research. The use of pulsed ultrasound with frequency of 1MHz, at 20%, with frequency modulation of 16Hz, 0.5 W/cm2 of intensity and application time of 5 minutes in acute osteochondral lesions showed similar statistical significance in chondral regeneration compared to the Control Group. In the application of USPSA (UNDERWATER PULSED ULTRASOUND) in the proliferative phase (third and fourth week) of acute osteochondral lesions there was a decrease in osteoblastic proliferation and formation of immature bone. Conclusions: There was an improvement in osteochondral regeneration with the use of the method, but ultrasonic emission parameters applied in the treatment of acute osteochondral lesions must continue to be studied, as these presented here constitute only one of the numerous therapeutic possibilities of this modality. DOI: 10.56238/pacfdnsv1-001